Acute kidney injury is associated with severe infection and fatality in patients with COVID-19: A systematic review and meta-analysis of 40 studies and 24, 527 patients. (November 2020) - Shao, Mengjiao; Li, XiaoMei; Liu, Fen; Tian, Ting; Luo, Junyi; Yang, Yining
Graphical abstract: Abstract: Currently, coronavirus disease 2019 (COVID-19) is spreading rapidly around the world. This study aimed to investigate whether the presence of acute kidney injury (AKI) might increase the risk of severe infection and fatality in COVID-19 patients. We searched the PubMed, Web of Science, ScienceDirect, MedRxiv and COVID-19 academic research communication platforms for studies reporting severe infection rates and case-fatality rates in COVID-19 patients with and without AKI up to June 20, 2020. The main outcomes were the comparisons of the severe infection rates and fatality rates in COVID-19 patients with and without AKI and the estimation of the odds ratio ( OR ) and its 95 % confidence interval (CI) for severe infection and mortality. Statistical analyses were performed with R statistical software. A total of 40 studies involving 24, 527 patients with COVID-19 were included in our meta-analysis. The incidence of AKI was 10 % (95 % CI 8%–13 %) in COVID-19 patients. The patients had higher severe infection and fatality rates (55.6 % vs. 17.7 % and 63.1 % vs. 12.9 %, respectively, all P < 0.01) with COVID-19. AKI was a predictor of fatality ( OR = 14.63, 95 % CI: 9.94–21.51, P < 0.00001) and severe infection ( OR = 8.11, 95 % CI: 5.01–13.13, P < 0.00001) in patients with COVID-19. Higher levels of serum creatinine (Scr) and blood urea nitrogen (BUN) were associated with a significant increase in fatality [Scr: mean difference (MD): 20.19 μmol/L, 95 % CI : 14.96–25.42, P < 0.001; BUN: MD : 4.07 mmol/L, 95 % CI: 3.33–4.81, P < 0.001] and severe infection (Scr: MD: 7.78 μmol/L, 95 % CI: 4.43–11.14, P < 0.00001, BUN: MD: 2.12 mmol/L, 95 % CI: 1.74–2.50, P < 0.00001) in COVID-19 patients. In conclusion, AKI is associated with severe infection and higher fatality rates in patients with COVID-19. Clinicians should pay more attention to the monitoring and treatment of COVID-19 patients with AKI.